Persistence and activation of right-wing political ideology - Davide Cantoni; Felix Hagemeister; Mark Westcott (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We argue that a long-run cultural persistence of right-wing ideology can explain the recent rise of right-wing populism. Shifts in the supply of party platforms can interact with this existing demand, and give rise to patterns of historical persistence. We study the context of Germany in the 2017 federal election, when the emergence of the AfD offered voters a populist right-wing option, with little social stigma attached. We show that municipalities that expressed strong support for the Nazi party in 1933 are more likely to vote for the AfD now, but not in 2013, when the AfD was a more moderate, fiscally conservative party. Using opinion surveys, we show that these dynamics are not generated by a concurrent demand shift: political attitudes do not shift sharply to the right in the municipalities with a history of Nazi support.
Keywords: D72; N44; P16; 330; Persistence; Culture; Right-wing ideology; Germany